ACYP1 Is a Pancancer Prognostic Indicator and Affects the Immune Microenvironment in LIHC - Zhou, Lingyi; Fu, Zheng; Wang, Shuai; Jia, Jing; Cheng, Yumeng; Zheng, Yunxiang; Zhang, Ningning; Lu, Wei; Yao, Zhi (Frontiers in Oncology, 2022)
Background: ACYP1 plays important physiological and metabolic roles in glycolysis and membrane ion pump activity by catalyzing acyl phosphate hydrolysis. ACYP1 is related to tumorigenesis and progression and poor prognosis in gastrointestinal cancer. However, its pancancer roles and mechanisms are unclear. Our study aimed to understand the ACYP1 expression signature and prognostic value across cancers and investigate immune infiltration patterns in liver hepatocellular carcinoma (LIHC) and verify them in LIHC samples. Methods: Transcriptional expression profiles of ACYP1 across cancers were analyzed using Oncomine and TIMER. The prognostic value of ACYP1 was assessed across PrognoScan, Kaplan—Meier Plotter, and GEPIA. Significant pathways associated with ACYP1 in LIHC were obtained via Gene Set Enrichment Analysis. The correlation between ACYP1 expression and immune infiltration in LIHC was investigated using TIMER. We validated ACYP1 expression, prognostic value, and association with immune cells in tumor tissues by immunohistochemistry and flow cytometry. Results: ACYP1 was overexpressed across cancers. High expression of ACYP1 correlated with a poor prognosis in most tumor types, especially in LIHC. ACYP1 was significantly implicated in immune and metabolic related pathways. High ACYP1 expression showed significant correlations with the abundances of Th2 cells, Tregs, macrophages, dendritic cells, and myeloid-derived suppressor cells in LIHC. LIHC patients with high ACYP1 expression showed significantly shorter overall survival and relapse-free survival rates concomitant with increased infiltration of CD4+ T cells. Mouse subcutaneous tumors with ACYP1 overexpression exhibited significantly accelerated tumor progression with increased aggregation of CD4+ T cells. Conclusion: Overall, ACYP1 may serve as a vital prognostic biomarker and play an immunoregulatory role in LIHC.